Toxicity of Melaleuca alternifolia essential oil to the mitochondrion and NAD(+)/NADH dehydrogenase in Tribolium confusum - Liao, Min (PeerJ, 2018)
BACKGROUND: In our previous study, Melaleuca alternifolia essential oil (EO) was considered to have an insecticidal effect by acting on the mitochondrial respiratory chain in insects. However, the mode of action is not fully understood. METHODS: In this study, we investigated the insecticidal efficacy of the M. alternifolia EO against another major stored-product pest, Tribolium confusum Jacquelin du Val. Rarefaction and vacuolization of the mitochondrial matrix were evident in oil-fumigated T. confusum adults. RESULTS: Alterations to the mitochondria confirmed the insecticidal effect of the M. alternifolia EO. Furthermore, comparative transcriptome analysis of T. confusum using RNA-seq indicated that most of the differentially expressed genes were involved in insecticide detoxification and mitochondrial function. The biochemical analysis showed that the intracellular NAD(+)/NADH ratio is involved in the differential effect of the M. alternifolia EO. DISCUSSION: These results led us to conclude that NAD(+)/NADH dehydrogenase may be the prime target site for the M. alternifolia EO in insects, leading to blocking of the mitochondrial respiratory chain.